Technology-Based Student-Centred ESP Writing With Genre-Based Teaching Approach (LSP International Journal, 2022)
Capitalising on current students’ preference for learning via technology, this article proposes a genre-based teaching approach for ESP writing employing the technology afforded for language learning. A module was designed to teach ESP writing to accounting students using sustainability reports as the basis. The module includes details of how to guide students to carry out genre analysis and corpus analysis in order to discover the language use in the reports. ESP students are reported to enjoy writing genres related to their disciplines where they are more prepared to participate. This is expected to be achieved with this module.